Candidosis on oral lichen planus - Kus Harijanti; Mintarsih Mintarsih (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2006)
Oral lichen planus (OLP) is a chronic inflammatory disease of the oral mucous membrane which is characterized by unpredictable exacerbation and remission. The pathognomonic of oral features of OLP are hyperkeratotic striation surrounded white patches of mucosal erythema are called Wickham’s Striae. Chronic inflammation or epithelial damage of the mucous membrane often followed by candidosis as secondary infection. Candida species are commensal microorganism, its population in oral cavity reach 70% of the oral microorganism. It is harmless, but it could become opportunistic pathogen when the condition of oral environment support, i.e. decrease of oral immune response or the oral microorganism ecosystem change. This purpose of the paper was to report the case of a female patient (49 years old) who came to the clinic of Oral Medicine Faculty of Dentistry Airlangga University Surabaya with clinical and mycological evidence of thrush (Oral acute pseudomembrane candidosis). The patient not only suffered thrush, but also chronic cervicitis vaginalis. So the patient also consumed the antibiotic which was given by gynecologist. The used of the antibiotic for chronic servicitis vaginalis was the contrary treatment of oral thrush, after treated with nystatin oral suspention, clinical examination showed clearly hyperkeratotic lesion (Wickham’s striae), and hystopathological test result showed that it was OLP. The chronic oral inflammation and epithelial damage (OLP) or antibiotic consumption could inhibited the candidosis treatment. The case report suggested that the first treatment should be given antimicotic if the mycological test of candidosis showed positive result.